2020
DOI: 10.1051/0004-6361/202037974
|View full text |Cite
|
Sign up to set email alerts
|

No universal connection between the vertical magnetic field and the umbra-penumbra boundary in sunspots

Abstract: Context. It has been reported that the boundary between the umbra and the penumbra of sunspots occurs at a canonical value of the strength of the vertical magnetic field, independently of the size of the spot. This critical field strength is interpreted to be the threshold for the onset of magnetoconvection. Aims. Here we investigate the reasons why this criterion, also called the Jurčák criterion in the literature, does not always identify the boundary between the umbra and the penumbra. Methods. We performed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 55 publications
3
11
0
Order By: Relevance
“…This result could be consistent with the work done by Lindner et al (2020), who studied the Jurčák criterion (Jurčák et al 2018). This is probably a stability criterion for the UM (though this is still an open discussion, see Löptien et al 2020). For this particular sunspot, they found that the Jurčák criterion applies to part of the LB, meaning it could be related to the part of the LB that has higher inclinations, while the tip would be ascribed to the fact that it is 'under evolution/formation'.…”
Section: Papersupporting
confidence: 90%
“…This result could be consistent with the work done by Lindner et al (2020), who studied the Jurčák criterion (Jurčák et al 2018). This is probably a stability criterion for the UM (though this is still an open discussion, see Löptien et al 2020). For this particular sunspot, they found that the Jurčák criterion applies to part of the LB, meaning it could be related to the part of the LB that has higher inclinations, while the tip would be ascribed to the fact that it is 'under evolution/formation'.…”
Section: Papersupporting
confidence: 90%
“…The penumbral filaments and umbral dots in the small spot are brighter than the ones in the large spot, even though their size is comparable. This decrease of the brightness of penumbral filaments was already reported by Löptien et al (2020).…”
Section: Discussionsupporting
confidence: 85%
“…They interpreted this constant value of B z to be the threshold for the transition from umbra to penumbra. However, their interpretation was later challenged by Löptien et al (2020), who attributed this constant B z to be caused by the decrease of the brightness of penumbral filaments with increasing spot size (see also Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jurčák et al (2018) suggested that the UP boundary occurs where the strength of the vertical magnetic field falls below a fixed threshold. However, this criterion (often called the Jurčák criterion) does not take into account the fact that the penumbra consists of both filaments and spines, the properties of which vary between spots of different sizes (Löptien et al 2020).…”
Section: Introductionmentioning
confidence: 99%